Federalism in India, origins and development - Mukarji, Nirmal K.; Arora, Balveer; Centre for Policy Research (New Delhi, India) (New Delhi : Vikas Pub. House, 1992)
Revisions of the papers read and discussed at a seminar held at the Centre for Policy Research, New Delhi, on 11-12 December 1987.
Includes bibliographical references.
Keywords: Federal government -- India